Development of Coagulation Factor Probes for the Identification of Procoagulant Circulating Tumor Cells - Tormoen, Garth W.; Cianchetti, Flor; Bock, Paul; McCarty, Owen (Frontiers in Oncology, 2012)
Metastatic cancer is associated with a hypercoagulable state, and pathological venous thromboembolic disease is a significant source of morbidity and the second leading cause of death in patients with cancer. Here we aimed to develop a novel labeling strategy to detect and quantify procoagulant circulating tumor cells (CTCs) from patients with metastatic cancer. We hypothesize that the enumeration of procoagulant CTCs may be prognostic for the development of venous thrombosis in patients with cancer. Our approach is based on the observation that cancer cells are capable of initiating and facilitating cell-mediated coagulation in vitro, whereby activated coagulation factor complexes assemble upon cancer cell membrane surfaces. Binding of fluorescently-labeled, active site-inhibited coagulation factors VIIa, Xa and IIa to the metastatic breast cancer cell line, MDA-MB-231, nonmetastatic colorectal cell line, SW480, or metastatic colorectal cell line, SW620, was characterized in a purified system, in anticoagulated blood and plasma, and in plasma under conditions of coagulation. We conclude that a CTC labeling strategy that utilizes coagulation factor-based fluorescent probes may provide a functional assessment of the procoagulant potential of CTCs, and that this strategy is amenable to current CTC detection platforms.